Pengaruh Total Quality Management (TQM) Terhadap Kinerja Innovatif : Pergolakan Pasar Sebagai Variabel Moderasi - Yesi Mutia Basri (Jurnal Ekonomi, 2012)
This paper examines the relationship between  Total Quality Management (TQM) and innovation performance, and  moderating effect market turbulence. The empirical data for this study was drawn from a survey of 58 middle/senior managers from services  firms in Pekanbaru. The analysis was conducted using Regression analysis. The findings indicate that TQM has not impact on innovative performance and  market turbulence moderated relationship TQM innovative performance.